The effect of moderate Intensity of low impact aerobic dance to the body flexibility in untrained elderly women - Santosa Budiharjo Santosa Budiharjo (Journal of the Medical Sciences (Berkala Ilmu Kedokteran), 2005)
Background: The body flexibility of elderly people tends to decrease. One of the causes is the increased dehydration of the tissues that leads to adhesion formation.Objective: To investigate the effect of moderate intensity of low impact dance on body flexibility in untrained elderly women.Methods: Pretest and posttest control design. A total amount of thirty, healthy women, untrained, 60 - 70 years old was divided into three groups. The first group was treated by exercise three times a week, the second group two times a week and the third group was the control group. The exercise used was D series of fitness dance for elderly created by PERWOSI Yogyakarta which is a low impact aerobic dance with moderate intensity (70 - 79 % Maximal heart rate), 40 - 54 minutes/day. Three groups are treated for eight weeks.Results: The result showed that the first group revealed a significant increase in body flexibility (p<0,05) in the fourth week. The second group also revealed statistically significant increase in body flexibility (p<0,05) in the eighth week. The changes of body flexibility of the first group was higher and significant different compared to the second group.Conclusion: The low impact aerobic dance with moderate intensity, 40 - 54 minutes/day, performed three times a week in untrained elderly women increase the body flexibility earlier and higher than that of twice a week. Key words: moderate intensity low impact aerobic dance - exercise frequency - body flexibility-elderly women